1996
DOI: 10.1002/(sici)1097-0304(199606)38:2<189::aid-ccd17>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of translesional hemodynamics: Comparison of pressure and flow methods in stenosis assessment in patients with coronary artery disease

Abstract: Aim of this study is the assessment of feasibility and clinical usefulness of a new index of stenosis severity, the slope of the instantaneous transstenotic pressure gradient/velocity relationship. Twenty‐one patients scheduled for percutaneous revascularization procedures were studied with simultaneous measurement of poststenotic coronary pressure and flow velocity, in basal condition and during maximal hyperemia induced with intracoronary papaverine. Reliable measurements of the transstenotic pressure gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…This study also raised a fundamental concern over correlating FFR and CFR values when drawing conclusions about myocardial ischaemia. In contrast to the study by Di Mario et al[58], Meimoun et al[59] showed that four patients with FFR value of 0.80 or less had a CFR value of more than 2.0 and two patients with FFR value of more than 0.80 showed CFR value of 2.0 or less, representing 12% of the patients in this study. A more recent retrospective cohort study[60] with 438 FFR and invasive CFR measurements showed that even though FFR is correlated to CFR (r = 0.34; P < 0.001), almost 40% of lesions show discordance between FFR and CFR.Johnson et al[60] demonstrated that neither invasive nor noninvasive CFR measurement techniques can be attributed to the discordance of FFR and CFR.…”
contrasting
confidence: 94%
See 1 more Smart Citation
“…This study also raised a fundamental concern over correlating FFR and CFR values when drawing conclusions about myocardial ischaemia. In contrast to the study by Di Mario et al[58], Meimoun et al[59] showed that four patients with FFR value of 0.80 or less had a CFR value of more than 2.0 and two patients with FFR value of more than 0.80 showed CFR value of 2.0 or less, representing 12% of the patients in this study. A more recent retrospective cohort study[60] with 438 FFR and invasive CFR measurements showed that even though FFR is correlated to CFR (r = 0.34; P < 0.001), almost 40% of lesions show discordance between FFR and CFR.Johnson et al[60] demonstrated that neither invasive nor noninvasive CFR measurement techniques can be attributed to the discordance of FFR and CFR.…”
contrasting
confidence: 94%
“…Di Mario et al[58] studied 21 patients, reporting r = 0.58 (P < 0.01), demonstrating a weak correlation between FFR and invasive CFR. In addition, their study showed that patients with an FFR value of 0.75 or less usually have a CFR value of 2.0 or less.…”
mentioning
confidence: 99%
“…Fifteen years later, the first ⌬P-v relationships of coronary stenoses in humans were obtained after placement of both a pressure and Doppler guidewire distal to the lesion. 11,12 Marques and coworkers 13 demonstrated the feasibility and reproducibility of this diastolic relationship and its ability to discriminate between normal and diseased coronary arteries.…”
Section: Interpretation Of the Pressure-gradient-flowvelocity Relatiomentioning
confidence: 99%
“…9,10 Diastolic pressure gradient-velocity (⌬P-v) relationships have been obtained in humans with 2 single-sensor-equipped guidewires. [11][12][13] Recently, the simultaneous measurement of phasic distal pressure and velocity by a single dual-sensor-equipped guidewire has become possible.…”
mentioning
confidence: 99%
“…6,20,30 This can be accomplished with a single wire equipped with two sensors, thanks to recent developments in wire technology. 31 These combined data allow the separate assessment of coronary stenosis and microvascular resistance, which has been successfully applied to develop improved concepts for diagnosis of coronary artery disease and evaluation of percutaneous interventions.…”
Section: Stenosis Assessment From Intracoronary Hemodynamics In the Cmentioning
confidence: 99%